Sex differences in the predictors of prisoner misconduct - Steiner, Benjamin (Criminal justice and behavior, 2014)
This study involved a comparison of the influences on inmate misconduct among female and male inmates. Data were collected from over 5,500 inmates housed in 46 facilities in Ohio and Kentucky (570 women and 5,059 men), and the relative effects of these inmates? background characteristics and confinement experiences were examined for sex-specific samples. The magnitudes of effects were then compared across the two groups. Findings revealed that background characteristics (e.g., age) and confinement experiences (e.g., involvement in education/vocational program) influence women?s and men?s odds of misconduct. Equality of coefficient tests revealed only three differences in the magnitude of these effects across the analyses of the sex-specific samples, suggesting there are far more similarities than differences in the predictors of misconduct among men versus women.